Clinical validation of the Unesp-Botucatu acute pain scale in sheep undergoing orthopedic surgery - Nuno Emanuel de Oliveira Figueiredo da Silva; Pedro Henrique Esteves Trindade; Gustavo Venâncio da Silva; Flávia Augusta de Oliveira; Marilda Onghero Taffarel; Mayara Travalini de Lima; Rubia Mitalli Tomacheuski; Gustavo dos Santos Rosa; Ana Liz Garcia Alves; Stelio Pacca Loureiro Luna (PLoS ONE, 2025)
Unesp-Botucatu sheep acute pain scale (USAPS) was validated for assessing postoperative abdominal pain. We aimed to investigate the clinical applicability and test the psychometric properties of USAPS to assess postoperative pain in sheep submitted to orthopedic surgery. Twenty-three healthy sheep undergoing patellofemoral joint arthrotomy were video-recorded for three minutes before and after surgery, after postoperative analgesic rescue, and 24 hours post-surgery. Four evaluators, unaware of the recording time points, randomly assessed all videos twice at one-month intervals. Intra-observer reliability based on the Intraclass Correlation Coefficient (ICC) was very good for all evaluators (ICC: 0.82–0.93). Inter-observer reliability was very good for four of six pairs of evaluators (ICC: 0.84–0.9) and good for two (ICC: 0.77 and 0.80). Principal component analyses and confirmatory factor analysis confirmed the USAPS´s unidimensional structure. The concurrent criterion validity had a strong Spearman correlation (rho: 0.80) between the USAPS and the Visual Analogue Scale. Responsiveness was evidenced by the highest USAPS total score 2 and 24 hours after surgery, and intermediate scores after analgesic rescue. USAPS items had an acceptable Spearman item-total correlation (rho: 0.38–0.64), except appetite (rho: 0.25). Internal consistency was excellent according to Cronbach’s alpha (α: 0.84) and acceptable according to McDonald’s omega coefficients (ω: 0.75). Specificity was 100% and sensitivity was 71%. USAPS cut-off point was ≥ 4 of 10, the same applied for soft tissue surgery. The area under the curve of 0.91 demonstrates the high discriminatory capacity of the scale. The item appetite can be excluded without affecting the USAPS cut-off point. We concluded that USAPS had satisfactory psychometric properties and, is a valid and reliable clinical tool for assessing pain in sheep undergoing orthopedic surgery.